Metal Complexes and Their Potential Therapeutic Role Against COVID-19: Recent Developments in Drug Designing - Kanwal Ashiq; Bushra Naureen; Sana Ashiq (Sudan Journal of Medical Sciences)
COVID-19 is a global pandemic caused by severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2). Being associated with high mortality rates, this pandemic has forced several countries worldwide to impose complete lockdowns to limit the spread of infection. Despite the development of various vaccines, there is still an urgent need to design novel treatments backed with safety data for fighting  SARS-CoV-2 and its various mutants. Currently, scientists are putting their strenuous efforts into finding the best treatment option for COVID-19. In this regard, metal complexes being active antiviral agents and immunity enhancers have great potential against SARS-CoV-2. Herein, metal complexes' therapeutic role and significance against treating SARS-CoV-2 or any of its target proteins are discussed.